Investigation of the Influence of the Space Orientation of Layers on the Surface Shape Error during Additive Shaping of Products by an Electric Arc in a Protective Gases Environment - Grechukhin Aleksandr (EDP Sciences, 2021)
The paper presents the results of a study of the process of additive surface shaping by an electric arc in a protective gas. An analysis was made of the errors in the shape of surfaces obtained with different filling of layers. It has been experimentally confirmed that such process parameters as the orientation of the layers, the coefficient of their overlap are significant and affect the numerical value of the error in the shape of the resulting surface. In this connection, they should be taken into account when designing algorithms for dividing into layers and filling them with additive shaping by an electric arc in a protective gas.